Le consensus brûle : le punk, violences et conflits en Allemagne de l’Est et de l’Ouest (1976-1982) - Pierre Raboud (Criminocorpus)
By comparing the case of East and West Germany, this paper aims to develop the different meanings which can be carried by violence within the punk scene. This topic is central in both scenes. It can be identified in songs’ lyrics and in fanzines’ visuals. Between proclamation and protest, violence can also adopt different meanings when taking the relations between the punk scene and society into account. Through the question of violence, this paper raises the issue of the historical and political meaning of punk and its ability to express and practice conflict.